2022
DOI: 10.1371/journal.pone.0270812
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between propofol and alfaxalone anesthesia for the evaluation of laryngeal function in healthy dogs utilizing computerized software

Abstract: Laryngeal paralysis is a well-documented cause of upper respiratory tract obstruction in canines. Diagnosis of laryngeal paralysis is usually made by visual evaluation of laryngeal motion whilst patients are under a light-plane of anesthesia. However, in human studies of laryngeal function evaluation, it has been shown that subjective scoring can lead to significant interobserver variance, which may cause false diagnosis. In this study, we propose to introduce a more objective method of assessing laryngeal fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The dog in this case report was administered butorphanol, followed by alfaxalone to facilitate the sedated oral exam. Previous studies have indicated that alfaxalone can falsely reduce arytenoid opening and movement after its administration ( 19 , 20 ), while other studies have found alfaxalone to be an acceptable alternative to propofol for laryngoscopy ( 17 , 18 ). In this specific case, the dose of alfaxalone used (total dose of 0.5 mg/kg IV) was lower compared to the doses described to negatively affect arytenoid motion ( 19 , 20 ) and enabled preservation of pharyngal and laryngeal function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dog in this case report was administered butorphanol, followed by alfaxalone to facilitate the sedated oral exam. Previous studies have indicated that alfaxalone can falsely reduce arytenoid opening and movement after its administration ( 19 , 20 ), while other studies have found alfaxalone to be an acceptable alternative to propofol for laryngoscopy ( 17 , 18 ). In this specific case, the dose of alfaxalone used (total dose of 0.5 mg/kg IV) was lower compared to the doses described to negatively affect arytenoid motion ( 19 , 20 ) and enabled preservation of pharyngal and laryngeal function.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that alfaxalone can falsely reduce arytenoid opening and movement after its administration ( 19 , 20 ), while other studies have found alfaxalone to be an acceptable alternative to propofol for laryngoscopy ( 17 , 18 ). In this specific case, the dose of alfaxalone used (total dose of 0.5 mg/kg IV) was lower compared to the doses described to negatively affect arytenoid motion ( 19 , 20 ) and enabled preservation of pharyngal and laryngeal function. The addition of doxapram, a centrally acting respiratory stimulant, could have been utilized however to further optimize laryngeal function in this case ( 19 , 21 ).…”
Section: Discussionmentioning
confidence: 99%